2017
DOI: 10.1016/j.gheart.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Sex Differences in the Prevalence and Awareness of Hypertension: An H3Africa AWI-Gen Study Across 6 Sites in Sub-Saharan Africa

Abstract: Background There is a high prevalence of hypertension and related cardiovascular diseases in sub-Saharan Africa yet few large studies exploring hypertension in Africa are available. The actual burden of disease is poorly understood and awareness and treatment to control it is often suboptimal. Objectives To report the prevalence of measured hypertension and to assess awareness and control of blood pressure among older adults in rural and urban settings in six sites located in west, east and southern Africa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
130
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(159 citation statements)
references
References 40 publications
(54 reference statements)
10
130
3
Order By: Relevance
“…Data on socio-demographic-, behavioural- and biological factors were collected via the translated (Se-Pedi) and pilot-tested paper questionnaire by trained field workers, and captured into REDCap, a secure web-based application [24]. Approximately 10% of all data entries were checked for accuracy as described in detail elsewhere [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Data on socio-demographic-, behavioural- and biological factors were collected via the translated (Se-Pedi) and pilot-tested paper questionnaire by trained field workers, and captured into REDCap, a secure web-based application [24]. Approximately 10% of all data entries were checked for accuracy as described in detail elsewhere [26]. …”
Section: Methodsmentioning
confidence: 99%
“…This number is thought to be an underestimate . A recent study across six sites in sub‐Saharan Africa found that despite South Africa having the highest blood pressure, 60% of men and 46% of women with hypertension in South Africa were unaware of it . Despite evidence of the increasing prevalence of multimorbidity in sub‐Saharan Africa, evidence of its impact on quality of life and hospitalisation is scarce .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the baseline data generated from this study has been demonstrated in several recent publications, including the identification of regional and sex differences in the prevalence of hypertension across SSA [60], and the six papers on BMI distribution in this special edition of Global Health Action [6772]. Manuscripts discussing the prevalence of diabetes, body composition and obesity, dyslipidemia, kidney disease, and smoking and alcohol consumption are currently in preparation.…”
Section: Discussionmentioning
confidence: 99%
“…As such, hypertension was defined as the presentation of one or more of the following conditions: previous diagnosis by a healthcare provider (which excluded cases of hypertension during pregnancy), taking medication for the condition, systolic blood pressure greater than 140 mm Hg and/or diastolic blood pressure greater than 90 mm Hg at the time of the study visit [60]. …”
Section: Methodsmentioning
confidence: 99%